The happy hippopotami - Martin, Bill, 1916-; Velde, Bob (New York, Holt, Rinehart and Winston, 1970)
Dozens of happy hippopotamuses have a fun-filled holiday at the beach.
Keywords: Hippopotamus -- Juvenile literature; Stories in rhyme; Hippopotamus -- Fiction